An assessment of acute and subchronic toxicity of Gas Anta Syrup in rodents - Duong, Dau Thuy; Anh, Pham Thi Van (Tạp chí Nghiên cứu Y học, 2026)
Gas Anta Syrup is a formulation derived from herbal ingredients, intended for the supportive treatment of peptic ulcers and gastroesophageal reflux disease. This study was conducted to evaluate the acute and subchronic toxicity of Gas Anta Syrup in Swiss mice. In the acute toxicity test, mice were administered increasing doses of the syrup to determine the minimum dose causing 100% mortality and the maximum dose causing 0% mortality. In the subchronic toxicity study, mice were divided into a control group and two treatment groups receiving the syrup at 4.32 and 12.96 mL/kg/day for 4 weeks. Parameters monitored included general conditions, body weight, hematological and biochemical indices, as well as gross and microscopic examinations of the liver and kidneys. Results indicated that at the maximum feasible dose of 100 mL/kg, no toxic manifestation or mortality was observed in the acute toxicity study. No significant difference was observed in the monitored indices between the treatment groups and the control group in the subchronic toxicity study. In conclusion, Gas Anta Syrup does not induce acute or subchronic toxicity in Swiss mice at the tested dosage levels.